(untitled) (Development Service Industry Management, 2025)
The study analyzes the issues of forming and implementing state policy to ensure the development of small and medium-sized businesses in the country. The focus is on the issues of ensuring the economic sustainability of small and medium-sized businesses. It is shown that representatives of this sector of the national economy have their own characteristics, associated with both advantages (high mobility, lower investments in creating and starting an activity, the possibility of using a simplified taxation and accounting system, preferential budget, credit, investment and other support programs), and the shortcomings (lower financial stability and safety margin, lower financial and resource capabilities, higher dependence on external environmental factors and conditions) of their management. However, the key conclusion is formed regarding the lower financial and economic resilience of small and medium-sized enterprises in terms of reducing their economic stability. The purpose of the article is to generalize and further develop methodological and applied principles and provisions of state policy regarding the formation and implementation of a mechanism for managing the economic stability of small and medium-sized business entities. The factors that weaken the economic stability of representatives of the small and medium-sized business sector in Ukraine in war conditions are indicated. The provisions have been developed, the concept, sequence and elemental composition of the mechanism for ensuring economic sustainability in the small and medium-sized business sector of Ukraine have been determined. Particular attention is paid to the factors of financial and innovative and technological support for the development and strengthening of the competitive positions of representatives of the analyzed sector of the economy.